Endophytic fungi of various medicinal plants collected from evergreen forest Baluran national park and its potential as laboratory manual for mycology course - Siti Murdiyah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Endophytic fungi found on a variety of medicinal plants may express particular benefit. These fungi provide an alternative to overcome the progressive microbial resistance and as an effort to combat infectious diseases that became one of the leading causes of mortality. The main objective of this study was to isolate endophytic fungi from leaf samples of five medicinal plants species collected from evergreen forests Baluran National Park and its use as laboratory manual for Micology. Research findings showed there were 3 isolates of endophytic fungi isolated from 2 medicinal plants namely Kesambi (Schleicera oleosa) and Ketapang (Terminalia catappa). All three isolates formed sporangiophores as asexual reproductive structures, while the structure of sexual still undiscovered therefore its classification has not been determined. The validity tests also showed that the lab manual is feasible for use with the percentage achievement 85.37% and 88.56%.